CITRA PEREMPUAN PADA BERITA KEKERASAN SEKSUAL: ANALISIS LINGUISTIK KORPUS - Fitriana; Nurul Fadzlin; Nabila Triana; Muh. Bahly Basri; Muhammad Ilham (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aimed to analyze the image of women in sexual violence news through a corpus linguistics approach to detik.com online news in the period 2023–2025. Using AntConc software, an analysis was conducted on the frequency, collocation, and concordance of the word "women" in the context of sexual violence news reporting. The results of the study showed that the word "women" most often appeared together with words such as "violence", "victims", and "sexual", which indicated the dominant narrative of women as vulnerable and in need of protection. Collocations such as violence against women and women's protection reinforce the image of women as objects of victimization. Furthermore, the concordance analysis revealed forms of political, economic, family, media, and legal victimization experienced by women. This study concluded that the media played a role in shaping public perceptions that strengthened patriarchal power relations and extend gender inequality systematically. Therefore, a fairer and victim-oriented reporting approach was needed in order to build social awareness that was gender-just.